A direct Z-scheme LaFeO3/WO3 photocatalyst for enhanced degradation of phenol under visible light irradiation. Issue 5 (October 2021) - Xu, Chang; Jin, Zehua; Yang, Jun; Guo, Fan; Wang, Pan; Meng, He; Bao, Guirong; Li, Zhi; Chen, Chen; Liu, Fenrong; Hu, Ruisheng
Abstract: A series of LaFeO3 /WO3 photocatalysts with different mass fractions were conceived and prepared by citric acid-assisted hydrothermal method. Including its structure, surface morphology, photornetrics and charge transfer, etc. were analyzed, which indicated that the establishment of a direct Z-scheme could enhance the photocatalytic performance significantly. Among them, the 15%-LaFeO3 /WO3 photocatalyst displayed the best photocatalytic performance (up to 94.15%) under 3 h visible light, even after 5 cycles, also shown the excellent photocatalytic stability. The excellent photocatalytic activity of constructed direct Z-scheme photocatalyst is mainly based on the physically more feasible migration of photogenerated carriers. In the other hand, according to the active species capture experiment and ESR spectra, the phenol degradation was mainly attributed to the oxidation reaction of ·OH and h + . Therefore, the photocatalytic reaction mechanism, degradative pathway and intermediate products under the visible light of the direct Z-scheme photocatalysts for phenol degradation were put forward. Graphical Abstract: ga1 The direct Z-scheme LaFeO3 /WO3 heterojunction photocatalyst was designed and exhibited the optimal activity for the phenol degradation under visible light up to 94.15% after 3 h under visible light irradiation. Highlights: There is no ideal method to deal with phenol, a toxic and refractory organic pollutant. Construct a direct Z-scheme LaFeO3 /WO3 photocatalyst to promote the separation of photogenerated electron-hole pairs. The degradation rate of phenol can reach up to 94.15% under 3 h visible light irradiation over LaFeO3 /WO3 . The photocatalytic degradation under visible light irradiation were proposed by 3D-EEMs and HPLC, etc.